Perancangan Aplikasi FinanSmart dengan Financial Health Score dan Family Link untuk Manajemen Keuangan Mahasiswa - Natasha Patricia Nainggolan; Nayla Anjani Nasution; Zevan Irfandi Surbakti (Bulletin of Computer Science Research, 2026)
Students often face difficulties in systematically managing their personal finances due to limited financial literacy and the absence of applications specifically designed for their needs. This condition can lead to consumptive behavior, inability to save, and prolonged financial dependency. This study aims to design and develop a web-based student financial management application named FinanSmart using the Research and Development (R&D) method with the Waterfall development model. The main innovations of this system include a Financial Health Score (FHS) mechanism calculated automatically each month as a quantitative indicator of students' financial health, and a Family Link feature that allows parents to monitor their child's financial condition in real-time while full privacy control remains with the student. Additionally, the system is equipped with spending pattern analysis, two-level budget notifications, daily reminders, and gamification elements to encourage consistent financial management. Functional testing using Black Box Testing on 18 test scenarios demonstrated a 100% success rate, proving that all features operate according to functional specifications. This system is expected to measurably improve students' financial awareness and behavior through personalized financial health score feedback and family-based monitoring features.